Gerda Walther: mysticism, philosophy, art - Burns, NE (2021)
This thesis examines the work of Gerda Walther, a philosopher and mystic whose work had until very recently been almost entirely neglected. A member of the Freiburg and Munich circles of phenomenologists, Walther worked in her main published texts (Ein Beitrag zur Ontologie der sozialen Gemeinschaften (1922) and Zur Phänomenologie der Mystik (1923)) to balance the competing impulses arising out of a radically atheistic Marxist upbringing, her study of philosophy, and the onset of what she describes as mystical and telepathic experiences. Walther’s work, seen more or less as failed interventions into conventional phenomenological discourse by several of her contemporaries, has been recently reassessed by philosophers, and presented as more successful than previously thought. I undertake a reorientation of emerging scholarship on Walther in terms of a meditative-mystical tradition, and in terms of German modernist writing: examining the overlooked conditions and cultural contexts that show their workings in Walther’s texts. I argue that Walther does indeed ‘fail’ to fit the mould of an early phenomenologist, and that this ironically staged failure forms the interest of her work.